Biochemistry demystified - Walker, Sharon, 4 Ph. D.0 16; (David M.) McMahon, David; 5 (New York : McGraw-Hill, 2008)
A comprehensive guide to biochemistry that covers each class of biomolecules, genetics, bioinformics, and other related topics, and includes time-saving tips, end-of-chapter quizzes, and a final exam.
The chemistry of biomolecules -- Cell structures and cell division -- Carbohydrates -- Lipids -- Lipid metabolism -- Protein structure -- Protein assembly and disassembly -- Nucleic acids and nucleotides -- Enzymes -- Glycolysis -- The citric acid cycle and oxidative phosphorylation -- Control of chemical processes signal biomolecules -- Specialty functions -- Bioinformation, analytical techniques, and bioinformatics.
Includes index.
Young Adult;Young Adult
Keywords: 2 -- 0; 6; Biochemistry.;Biochemistry.;Biochemistry.; 20; 2